Why Do Some Primary Care Practices Engage in Practice Improvement Efforts Whereas Others Do Not? - Goldberg, Debora Goetz (Blackwell Science Inc, 2013)
OBJECTIVE: To understand what motivates primary care practices to engage in practice improvement, identify external and internal facilitators and barriers, and refine a conceptual framework. DATA SOURCES: In-depth interviews and structured telephone surveys with clinicians and practice staff (n = 51), observations, and document reviews. STUDY DESIGN: Comparative case study of primary care practices (n = 8) to examine aspects of the practice and environment that influence engagement in improvement activities. DATA COLLECTION METHODS: Three on-site visits, telephone interviews, and two surveys. PRINCIPAL FINDINGS: Pressures from multiple sources create conflicting forces on primary care practices' improvement efforts. Pressures include incentives and requirements, organizational relationships, and access to resources. Culture, leadership priorities, values set by the physician(s), and other factors influence whether primary care practices engage in improvement efforts. CONCLUSIONS: Most primary care practices are caught in a cross fire between two groups of pressures: a set of forces that push practices to remain with the status quo, the “15-minute per patient” approach, and another set of forces that press for major transformations. Our study illuminates the elements involved in the decision to stay with the status quo or to engage in practice improvement efforts needed for transformation.